The soup movement - Davis, Ben, 1985 or 1986- (Oxford University Press, 2020)
To aid his recovery from a life-threatening illness Ethan and his family move out of the city for a healthy new start. Ethan's getting enough funny looks as the new boy at school as it is, without his Mum giving him homemade soup every day for lunch! But when Ethan meets a homeless man called Harry, and gives him the soup, it is the start of an unlikely friendship. Soon the two of them begin giving soup to the other homeless people around town and when his sister shares their antics on Instagram the #SOUPMOVEMENT begins-they even make it on the news!